Reservoir Characteristics and Main Controlling Factors of the Aershan Formation in the Shana Sag of the Erlian Basin - Tang, Jingrun (International Journal of Natural Resources and Environmental Studies, 2025)
The exploration and development of the Erlian Basin is long, and the Shana Sag located in the central part of the basin is a relatively underexplored new block, with little previous research conducted on this area. The Aershan Formation in this block has significant development potential. To achieve efficient development of the Aershan Formation oil reservoir in the Shana Sag, this article will combine previous data to study the petrological characteristics, pore throat characteristics, and physical properties of the reservoir rocks in the study area, and carry out favorable reservoir classification. The results indicate that the reservoir lithology of the Aershan Formation in the study area is primarily composed of pebbly, unevenly sized, fine to medium-grained sandstone, lithic sandstone and feldspathic lithic sandstone, with fillings mainly consisting of cement and argillaceous matrix. The average porosity of the reservoir is 14.5%, and the average permeability is 4.61 mD, making it a medium-porosity and extremely low-permeability reservoir. The pore types are primarily primary intergranular pores and dissolved intergranular pores, and the pore structure belongs to the small pore and medium-fine throat type. Based on characteristic parameters, the reservoir is divided into three categories; sedimentation and diagenesis play a crucial role in the formation of favorable reservoirs.